On human nature - Turner, Jonathan H., author.
1 online resource.
Keywords: "This new book by the distinguished sociological theorist Jonathan H. Turner combines sociology, evolutionary biology, cladistic analysis from biology, and comparative neuroanatomy to examine human nature, as it was inherited from the common ancestors that humans shared with present-day great apes. This inherited legacy was altered by selection pressures on these ancestors of humans-termed hominins for being bipedal-to get better organized than extant great apes as they were forced from the forest canopies to open country terrestrial habitats. The effects of these selection pressures made humans' hominin ancestors more social and group oriented by increasing their emotional capacities. This, in turn, enabled further selection for a larger brain, articulated speech, and culture along the human line. Turner elaborates human nature as a series of overlapping complexes that are the outcome of the inherited legacy of great apes being fed through the transforming effects of a larger brain, speech, and culture. These complexes, he shows, can be understood as the cognitive complex, the psychological complex, the emotions complex, the interaction complex, and the community complex"--